2016
DOI: 10.1111/iep.12200
|View full text |Cite
|
Sign up to set email alerts
|

Fish pollutants MeHg and Aroclor cause permanent structural damage in male gonads and kidneys after prepubertal exposure

Abstract: This study investigated whether or not prepubertal exposure to the fish contaminants methylmercury (MeHg) and the polychlorinated bisphenol Aroclor in low doses interferes with the histomorphometry of the testes, epididymis, liver and kidneys in rats. Wistar male rats, 21 days old, were allocated into the following: control (n = 17, received corn oil), MeHg (n = 17, received MeHg at 0.5 mg/kg/day), Aroclor (n = 17, received Aroclor at 1.0 mg/kg/day), low mix (n = 18, received MeHg at 0.05 mg/kg/day and Aroclor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Nowadays, it is well-known that testis function is a primary target of a large number of pollutants. Delayed establishment of spermatogenesis (295), impaired differentiation of internal and external male genital structures (296), reduced sperm production and disruption of the hypothalamic–pituitary–gonadal axis (297), decreased anogenital distance and decreased prostate and seminal vesicle weights (298, 299), among others, represent just some of the multiple observations performed.…”
Section: Pharmacological Agents and Xenobiotics May Affect Sertoli Cementioning
confidence: 99%
“…Nowadays, it is well-known that testis function is a primary target of a large number of pollutants. Delayed establishment of spermatogenesis (295), impaired differentiation of internal and external male genital structures (296), reduced sperm production and disruption of the hypothalamic–pituitary–gonadal axis (297), decreased anogenital distance and decreased prostate and seminal vesicle weights (298, 299), among others, represent just some of the multiple observations performed.…”
Section: Pharmacological Agents and Xenobiotics May Affect Sertoli Cementioning
confidence: 99%
“…Histopathological analysis demonstrated varied changes in renal and hepatic tissue in all treatments, although this damage was generally most frequent and intense in the animals of the MeHg group. Renal alterations promoted by MeHg, such as hypertrophied glomeruli and tubular lesions, had already been demonstrated in small rodents by Garcia et al ( 23 ) and Khan et al ( 24 ), respectively. Damage caused by mercury compounds, such as those found in the present study, was also identified in the liver of these mammals, ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 70%
“…Accordingly, gonad abnormalities of fish have been associated, among others, with genetic quality and hybridization status of the broodstock [18,19], autoimmune disease [20], changes in physical water parameters [21,22] or parasite infection [23,24]. One environmental factor that has attracted particular attention as a cause of gonad abnormalities in fish is aquatic contamination by anthropogenic chemicals [4,15,[25][26][27][28][29][30]. Obviously, a broad variety of factors can be involved in the induction of gonad morphological alterations in fish, and to advance our understanding of this phenomenon, it needs a systematic approach to unravel the causative factors and processes.…”
Section: Introductionmentioning
confidence: 99%